IOT BASED HOME SAFETY GAS LEAKAGE DETECTION AND AUTOMATIC BOOKING SYSTEM - Christal Mary .S, Suma; Leela.R, Josphine; .R, Vedhapriyavadhana; Rajathi.G, Ignisha (International Journal of Psychosocial Rehabilitation, 2024)
Gas spillages causes a significant issue in family unit, in this way the proposedgas spillage identification and checking framework is created There are numerousstrategies accessible for booking a Gas Refill, techniques incorporate web based booking,telephonic booking and so on. It will be difficult situation for the individual who uses LPGgas for cooking reliably. The aim of this paper is to introduce another frameworkconsequently books a cylinder at the point when the gas is going to discharge is bysendinga notice to the gas office using Wifi using Internet of Things approach In addition to thatsensor is utilized to identify gas spillage at home. On the off chance that the gas spillage issensed, the gadget continues ahead with ringer caution and showing ready message inLCD show at the same time switch on the fumes fan and turn over the DC engine, is madeto kill the gas regulator, PIR sensor additionally put in the home to inform about the humannearness. In the event that no individual, naturally power off simultaneously the noticewill be sent to client through versatile by notice calls and SMS. Wifi is one of the mostutilized systems over the world. Henceforth, load cell has been utilized to screen theheaviness of the LPG gas consistently. The values are next taken care of to the Arduinomicrocontroller. By utilization of GSM Module, the data is sent to client by SMS andfurthermore programmed booking is finished by dialing the enlisted gas booking number.Consequently, answer warning will be sent to the client about the booking status. This,work this causes the general public to explicitly demonstrate gas spillage and  furthermore helps the two clients and the office to get the gas booking made consequentlyutilizing the IOT procedure